Pengaruh Nanofilled Resin Coating terhadap Kekasaran Permukaan Semen Ionomer Kaca - Michael William Handoko; Rosalina Tjandrawinata (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2019)
One of the restorative dental materials that is continuously developed is Glass Ionomer Cement (GIC). The aim of this research is to know whether there is influence of nanofilled resin coating application on GIC to reduce surface roughness. In this study GIC type II (EQUIA Forte, GC, Japan) was used to be mechanically manipulated and inserted into a mold which produced a sample of 6.0±0.3 mm in diameter and 3.0±0.2 mm in height. GIC samples were divided into 2 groups namely 10 GIC samples were not coated with nanofilled resin coating as control group and 10 GIC samples were coated with nanofilled resin coating as treatment group. GIC samples were tested immediately and then immersed in sterile distilled water in a 37°C incubator. After 24 hours, GIC samples were surface roughness tested using a Surface Roughness Tester. Then all samples were brushed using a soft bristle mechanical tooth brush for 1 hour. After brushing, the sample is tested for final surface roughness. The results showed an increase in surface roughness in non-coated group/control (0.005 ± 0,328mm) and coated group (0.015±0.240 mm). Statistical data analysis using unpaired t test showed that there was no significant difference (p>0.05) in the increasing of surface roughness between control group and treatment group. It can be concluded that application of nanofilled resin coating to GIC cannot reduce the roughness of GIC surface.